What's the worst that could happen? - Westlake, Donald E. (Thorndike, Me., USA : Bath, Avon, England : Thorndike Press ; Chivers Press, 1996)
Dortmunder is in the midst of a routine burglary of a Long Island mansion when who shows up toting a gun but the owner, nasty billionaire Max Fairbanks. Worse, Fairbanks takes Dortmunder's supposedly lucky ring. Highly insulted, Dortmunder and his gang execute their own peculiar reign of terror, and although they acquire quite a bit of Fairbanks' swag, they never quite get the ring back. Which leads Dortmunder to wonder precisely what sort of luck the ring carries.
74095
Keywords: Large type books; Dortmunder (Fictitious character) -- Fiction; Criminals -- Fiction; Detective and mystery stories; Humorous stories